Heritability of complex white matter diffusion traits assessed in a population isolate. Issue 2 (5th November 2015) - Kochunov, Peter; Fu, Mao; Nugent, Katie; Wright, Susan N.; Du, Xiaoming; Muellerklein, Florian; Morrissey, Mary; Eskandar, George; Shukla, Dinesh K; Jahanshad, Neda; Thompson, Paul M.; Patel, Binish; et al.
Abstract: Introduction: Diffusion weighted imaging (DWI) methods can noninvasively ascertain cerebral microstructure by examining pattern and directions of water diffusion in the brain. We calculated heritability for DWI parameters in cerebral white (WM) and gray matter (GM) to study the genetic contribution to the diffusion signals across tissue boundaries. Methods: Using Old Order Amish (OOA) population isolate with large family pedigrees and high environmental homogeneity, we compared the heritability of measures derived from three representative DWI methods targeting the corpus callosum WM and cingulate gyrus GM: diffusion tensor imaging (DTI), the permeability‐diffusivity (PD) model, and the neurite orientation dispersion and density imaging (NODDI) model. These successively more complex models represent the diffusion signal modeling using one, two, and three diffusion compartments, respectively. Results: We replicated the high heritability of the DTI‐based fractional anisotropy ( h 2 = 0.67) and radial diffusivity ( h 2 = 0.72) in WM. High heritability in both WM and GM tissues were observed for the permeability‐diffusivity index from the PD model ( h 2 = 0.64 and 0.84), and the neurite density from the NODDI model ( h 2 = 0.70 and 0.55). The orientation dispersion index from the NODDI model was only significantly heritable in GM ( h 2 = 0.68). Conclusion: DWI measures from multicompartmental models were significantly heritable in WM and GM. DWI can offer valuable phenotypes for genetic research; and genes thus identified may reveal mechanisms contributing to mental and neurological disorders in which diffusion imaging anomalies are consistently found. Hum Brain Mapp 37:525–535, 2016 . ©2015 Wiley Periodicals, Inc.